Pengembangan Perangkat Pembelajaran Science, Environment, Technology and Society (SETS) Untuk Meningkatkan Pemahaman Konsep dan Sikap Peduli Lingkungan Siswa Sekolah Dasar: Development of Science, Environment, Technology and Society (SETS) Learning Tools to Improve Concept Understanding and Environmental Concern for Elementary School Students - Mahlianurrahman, Mahlianurrahman (Pedagogia : Jurnal Pendidikan, 2017)
This study aims to (1) produce a SETS kit that is feasible to the understanding of concept and caring environmental of Elementary School (2) find out the effectiveness of the SETS kit to the understanding of concept and caring environmental. This study is a research and development refering to the opinion of Borg & Gall. The design of learning kits consists of ten steps, including (1) research and information collection; (2) planning; (3) developing preliminary form of draft product; (4) preliminary field testing; (5) main product revision; (6) main field testing; (7) operational product testing; (8) operational field testing; and (9) final product revision; (10) dissemination. Subjects were students of Elementary School 3 Kota Fajar. The results show that the learning kit is effective to understanding of concept and caring environmental of students according to the material expert and learning expert with excellent ratings category. Based on the result show that there are significant differences in understanding of concept and caring environmental of students who take the study with SETS kits with those who do not use learning kits.